2017
DOI: 10.1371/journal.pmed.1002213
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito-Disseminated Insecticide for Citywide Vector Control and Its Potential to Block Arbovirus Epidemics: Entomological Observations and Modeling Results from Amazonian Brazil

Abstract: BackgroundMosquito-borne viruses threaten public health worldwide. When the ratio of competent vectors to susceptible humans is low enough, the virus’s basic reproductive number (R0) falls below 1.0 (each case generating, on average, <1.0 additional case) and the infection fades out from the population. Conventional mosquito control tactics, however, seldom yield R0 < 1.0. A promising alternative uses mosquitoes to disseminate a potent growth-regulator larvicide, pyriproxyfen (PPF), to aquatic larval habitats;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 42 publications
1
68
1
Order By: Relevance
“…Mosquito-disseminated Pyriproxyfen is another novel control strategy being used in Brazil, with promising results regarding the reduction of field populations of Ae. aegypti and the predicted number of dengue cases [ 98 , 99 ].…”
Section: Control and Prevention Strategiesmentioning
confidence: 99%
“…Mosquito-disseminated Pyriproxyfen is another novel control strategy being used in Brazil, with promising results regarding the reduction of field populations of Ae. aegypti and the predicted number of dengue cases [ 98 , 99 ].…”
Section: Control and Prevention Strategiesmentioning
confidence: 99%
“…Furthermore, the use of growth regulators is not limited to the administration to breeding sites but can be extended to adult vector control in integrated approaches. Insect growth regulators are available for different modes of application, ranging from time release granules to powders and have recently been used at large scale to curb the zika epidemic in Brazil 31 .…”
Section: Improving Cost Effectiveness -Implications Of the Emira Projectmentioning
confidence: 99%
“…Another novel strategy involving infection of A. aegypti with Wolbachia bacteria [9] has revealed remarkable decline in transmission capability of A. aegypti for range of arboviral infection including yellow fever. Recently, a similar study [10] revealed striking outcomes of pyriproxyfen (synthetic analogue of insect juvenile hormone) in curtailing the transmission capacity of A. aegypti. From the preliminary trials and studies on Figure 1.…”
mentioning
confidence: 98%